Times of History, Times of Nature : Temporalization and the Limits of Modern Knowledge. - Ekström, Anders; Bergwik, Staffan (New York, NY : Berghahn Books, Incorporated, 2022)
No detailed description available for "Times of History, Times of Nature".
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books